MAKA KITA BERSERU,“ALLAH, BAPA YANG MAHARAHIM”: Membaca Alkitab dari Perspektif Perempuan - Simanullang, Banggas (UNIKA Santo Thomas, 2008)
There are different responses given to the question: “Is the Bible really disparaging the women?” Literally speaking, it is that we find clear, explicit cases of the marginalization or segregation of women in several passages of the Bible, both in the Old and the New Testaments. These texts sound strange and surprising to one who is not familiar with the culture of the biblical world and believes in a just and liberating God. Therefore, a reading from a woman’s perspective is indispensable as a guarantee that the Bible’s God is also on the side of them. To read the Bible from a woman’s perspective, we must read it with women’s eyes, that is to say, conscious of the existence of individuals who are cast aside because of their sex. For this reason our reading does not come out spontaneously, and a conscious effort is needed to discover new women-liberating aspects or even elements in the text that other perspectives would not bring to light. Feminist consciousness is a basic skill indispensable to read the Bible from woman’s perspective.